Wavelength dependence of linear birefringence and linear dichroism of Bi2− x Pb x Sr2CaCu2O8+ δ single crystals - Keigo Tokita; Kenta Nakagawa; Kun Zhang; Komei Okano; Masataka Matsumoto; Takuya Nakanishi; Masaki Fujita; Toru Asahi (Scientific Reports)
Abstract Copper oxide high-temperature superconductors, such as Bi2Sr2CaCu2O8+ δ (Bi2212), have garnered extensive research interest due to their high critical temperatures (T c) surpassing the Bardeen–Cooper–Schrieffer (BCS) limit. The two-dimensional CuO₂ plane is widely regarded as the most crucial element of high-T c cuprate superconductors. The anisotropy of this CuO₂ layer remains a topic of ongoing interest. Although a few experimental results have reported strong optical anisotropy in both ab and ac-planes of Bi2212 through optical “reflectivity” measurements, there is a lack of studies focusing on the optical anisotropy of these materials using optical “transmittance” measurements by utilizing ultraviolet and visible light. Using a generalized high-accuracy universal polarimeter, we observed significant linear birefringence and linear dichroism peaks in the UV region at room temperature. To investigate the origin of the significant optical anisotropy, single crystals of Bi2− x Pb x Sr2CaCu2O8+ δ with different lead contents (x = 0, 0.4, and 0.6) were grown using the floating zone method, and the wavelength dependencies of linear birefringence and linear dichroism along the c axis were measured. The insights gained into the optical anisotropy of Bi2− x Pb x Sr2CaCu2O8+ δ from this study are significant for discussing its origin of the mechanism of high-T c superconductivity.